GOD'S PRESENCE AMID WOMEN'S MARGINALIZATION AND SUFFERING: A CONTEXTUAL THEOLOGICAL PERSPECTIVE ON GENDER AND GOD'S JUSTICE - Gomgom Simorangkir; Riris Johanna Siagian (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study highlights God's presence amidst the marginalization and suffering of women, particularly in the context of Batak culture, which remains steeped in patriarchal values. Using a qualitative approach and a contextual theology paradigm, this study reinterprets women's experiences as a locus theologicus to understand God's justice and provision. Women's marginalization is evident in various social, customary, and ecclesiastical aspects, where women are often positioned as "controlled" and denied full space in decision-making. Yet, Scripture demonstrates that God sides with the oppressed and upholds justice for marginalized groups. The story of Hagar, Jesus' ministry to the Samaritan woman, and the testimony of the resurrection entrusted to women affirm God's liberating presence and the restoration of human dignity. In light of the Holy Spirit's work, the church is called to transform gender relations equitably, transcending the boundaries of cultural patriarchy. Contextual theology serves as a critical tool for rereading Batak customs, particularly dalihan na tolu, so that their values ​​are lived out in the spirit of equality and justice in the Gospel. Thus, God's presence is not merely a theological discourse, but is evident in the solidarity, struggle, and liberation of women from oppressive social structures. The church is expected to be a prophetic community that presents signs of God's justice in an inclusive and transformative way in society.